Environmental Journalism in Nigeria: Representation of Climate Change in Nigeria - Ukpong, Ifiokobong Isong Ukpong (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
Climate change, which can be described as a change in the average weather condition over a period of time, has become a serious problem in the 21st century. The result and impacts of climate change are reported to be severe and harsh, this includes flood, famine, drought, etc. It is regarded as one of the most serious environmental issues, thus there is a need to create maximum awareness about it. The media as an important source of information has a part to play in creating the needed awareness for the public. Through media coverage of climate change, the public learns and understands the phenomenon and how to mitigate its effects. How the media frame climate change issue is important to how the citizens will react to the situation. Hence, this study examines how the Nigerian newspapers frame and present the climate change issue. Adopting a quantitative content analysis, this study analyzed n=303 news articles published between January 1, 2015, and December 31, 2019, in four newspapers; Punch, Vanguard, Guardian, and ThisDay Newspaper. The findings of this study suggest that there are two most commonly used themes by the newspapers to present climate change issues. These two themes were the “effects” and “mitigation” themes. The study also found that as regards the use of tone in the newspapers’ presentation, a negative tone was most used. This is as a result of the dominant frame “effect frame” used in the reports. Similarly, this study found that the majority of the climate change issue was reported as straight news and the source of the news is largely the reporters themselves. The study concluded that climate change is not given enough attention by the Nigerian media which is at the detriment of the country and its citizens. This study recommended that Nigerian media should bestow equal attention given to political issues in the country should also be attached to the climate change issue. Lastly, the media should employ the use of adaptation frame more, this is due to the economic conditions of the country. Keywords: climate change, environmental journalism, media analysis, news content, Nigerian press

ÖZ: Son yıllarda hava koşullarında meydaa gelen değişiklik olarak tanımlanabilecek iklim değişikliği, 21. yüzyılda ciddi bir sorun haline gelmiştir. İklim değişikliğinin sonuçlarının ve etkilerinin şiddetli ve sert olduğu bildirilmektedir. Buna sel, kıtlık, ve kuraklık da dahildir. Bu en ciddi çevre sorunlarından biri olarak kabul edilir, bu nedenle bu konuda maksimum farkındalık yaratmaya ihtiyaç vardır. Önemli bir bilgi kaynağı olarak medya, halk için gerekli farkındalığı yaratmada önemli bir rol oynamaktadır. İklim değişikliğinin medyada yer alması aracılığı ile halk, olguyu ve etkilerini nasıl hafifleteceğini öğrenir ve anlar. Medyanın iklim değişikliği konusunu topluma nasıl servis ettiği, toplumun duruma nasıl tepki vereceği açısından önem arz etmektedir. Bu çalışma Nijeryalı gazetelerin iklim değişikliği konusunu basında nasıl çerçevelediğini ve sunduğunu inceliyor. Nicel bir içerik analizi benimseyen çalışma, 1 Ocak 2015 ile 31 Aralık 2019 tarihleri arasında çevre ile ilgili yayınlanan 303 haber makalesini dört gazetede analiz etti; Punch, Vanguard, Guardian ve ThisDay gazeteleri. Bu çalışmanın bulguları, gazetelerde iklim değişikliği konularını sunmak için en sık kullanılan iki çerçeve olduğunu göstermektedir. Bu iki çerçeve “etkiler” ve “hafifletme” çerçeveleridir. Çalışma esnasında aynı zamanda gazetelerin sunumunda ton kullanımıyla ilgili olarak en çok olumsuz tonun kullanıldığını tespit edildi. Bu, raporlarda kullanılan baskın çerçeve “etki çerçevesi”nin bir sonucudur. Benzer şekilde, bu çalışma iklim değişikliği sorununun çoğunun sıradan haber olarak bildirildiğini ve haber kaynağının büyük oranda gazetecilerin kendileri olduğunu bulmuştur. Bu çalışma, ülkenin ve vatandaşlarının zararına olan iklim değişikliğinin Nijerya medyası tarafından yeterince dikkate alınmadığı sonucuna vardı. Bu çalışma, Nijerya medyasının ülkedeki siyasi meseleler kadar iklim değişikliğine de eşit miktarda dikkat göstermesi gerektiğinin eklenmesini önerdi. Çalışma, basının bu meseleyi ülkenin ekonomik koşulları çerçevesinde daha fazla odaklanarak kullanması gerektiği önerisi ile sonlandırılmıştır. Anahtar kelimeler: iklim değişikliği, çevre gazeteciliği, medya analizi, içeriği, Nijerya basını
Master of Arts in Communication and Media Studies. Institute of Graduate Studies and Research. Thesis (M.A.) - Eastern Mediterranean University, Faculty of Communication, Dept. of Communication and Media Studies, 2020. Supervisor: Assist. Prof. Dr. Nilüfer Türksoy.
Keywords: Communication and Media Studies; Environmental Journalism--Nigeria; Environmental Protection--Press Coverage; Mass media and the environment--Nigerian Press; Climatic changes in mass media; Environmental policy--Nigeria; Communication in the environmental sciences; Environmentalism; Climate change; environmental journalism; media analysis; news content; Nigerian press